Assessment of Rail System Lines for Timetable Optimization with Neutrosophic AHP and TODIM Integration - Yüksel, Taha (Uluslararasi Muhendislik Arastirma ve Gelistirme Dergisi, 2026)
Urban rail systems are vital components of public transportation in large cities, where passengers often rely on transfers between lines. However, fully synchronizing timetables across all transfer stations is challenging due to the complexity of these networks. This study aims to develop a framework for timetable synchronization by prioritizing urban rail lines based on their relative importance, rather than just transfer passenger volumes. A hybrid multi-criteria decision-making approach is proposed, combining the Interval-Valued Neutrosophic Analytic Hierarchy Process with the TODIM method. This approach incorporates expert judgments, considers uncertainty, and reflects behavioral decision patterns like risk perception and reference dependence. The model is applied to selected lines in Istanbul's urban rail system, using criteria such as passenger density, transfer connectivity, travel time, and service frequency. Results show that the M2 (Yenikapı–Hacıosman) line is the most critical for synchronization, followed by the M4 line, based on operational and structural factors. The proposed framework offers a more adaptable and informed strategy for optimizing train schedules, aiming to reduce waiting times at key transfer stations and enhance passenger satisfaction. Due to its simplicity, this framework is suitable for urban transport networks and can adapt to future transport demand changes.